Analisis Literasi Keuangan di Era Digital Siswa SMA N 2 Mataram - Dewa Ayu Putu Yuliani; Rizky Maulana Hidayat; Dewi Lestari Putri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid development of digital technology has transformed the landscape of personal financial management, particularly among younger generations. This study aims to analyze the level of financial literacy among students at SMA Negeri 2 Mataram in the context of the digital era, focusing on their understanding of basic financial concepts, financial behavior, and the use of financial technology (fintech). The method employed is a quantitative descriptive approach, with data collected through questionnaires distributed to 120 students in grades XI and XII. The data were analyzed using descriptive statistics and correlation tests to examine the relationship between financial literacy levels and the use of digital financial applications. The results indicate that most students have a limited understanding of basic financial knowledge, especially in terms of budgeting, saving, and digital investment. However, the majority of students are familiar with using digital applications such as e-wallets and mobile banking, although their usage tends to be more consumptive rather than productive. The findings also reveal a significant relationship between the intensity of using digital financial applications and the level of students’ financial literacy. This study recommends the integration of digital-based financial literacy materials into the school curriculum, as well as practical training relevant to adolescents’ needs in the technological era. Improving financial literacy from the secondary school level is considered crucial in shaping a generation that is wise and responsible in managing personal finances.